Embedded system / Leong Keat Poh - Leong , Keat Poh (2005)
Efficiency is a very important issue for a doctor because in the medical field, every minute even a second can save a persons life. But one of the major problems which the doctors are facing is that they are not being able to attend to all their patients because some of them are just too busy or the patient need to wait for a long time in order to meet the doctor. In order to solve this situation, Doctor's personal management system (DPMS) has been developed. DPMS is a pocket pc application that helps doctors to plan their schedule, appointments, keep personal data and contacts of their friends and also patients. With DPMS, hopefully the efficiency and productivity of the doctors will be increased and in the process, it will also satisfy the patients because they are able to meet the doctors on time and to get their treatment.